Peri conceptional association of the triad of hyperhomocsteinemia, hypothyroidism and impaired carbohydrate metabolism with recurrent pregnancy loss - Gadwal, Bhagyashree Mallinath; Rajan, Revathi S.; Rao, Kamini A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Recurrent pregnancy loss is a cause of great concern to the affected couple as well as the treating physician. We evaluated the periconceptional association of the triad of hyperhomocystienemia, hypothyroidism, and impaired carbohydrate metabolism with RPL and to identify the potential risk factors for RPL which are probably nutritional. Methods: Seven hundred ninety-six consecutive pregnancies with two or more abortions referring to our Infertility clinic were selected to be studied in a descriptive, prospective observational study in 2012-2014. All the pregnant women were subjected to routine blood tests/ examination/ imaging as per hospital protocols. All underwent TSH, FT4, GTT 75 gm (fasting and 2 h postprandial) as per routine antenatal workup. Additionally, fasting plasma homocysteine, antinuclear antibody, anti phospholipid antibody, anti- thyroid peroxidase antibody tests were performed for patients with RPL. All the patients were studied for the triad of hypothyroidism, hyperhomocysteinemia and impaired carbohydrate metabolism. Results: The incidence of RPL was found to be 5.65 %. Majority of women (51.1%) were in the age group 30-34 years. Majority of the women (55.6%) had 2 previous abortions. Majority of women (57.7%) had conceived normally. Majority of women (46.7%) had BMI<25. PCOS was reported in 28.9% women. HHcy, hypothyroidism and impaired carbohydrate metabolism was found in 78%, 73% and 73% women, respectively. The presence of two factors was reported in 60 to 65% women. 56% women reported the presence of the triad. About 7% of the patients underwent repeat abortion in second trimester of which 66.6% had the association of triad. Conclusions: Investigating these three factors in patients with RPL would help in early recognition, monitoring, and aggressive surveillance, which will help prevent obstetric complications. Simple nutritional correction may allow for better maternal and fetal programming and appropriate risk modulation.